Primary Localized Cutaneous Nodular Amyloidosis and Limited Cutaneous Systemic Sclerosis: Additional Cases with Dermatoscopic and Histopathological Correlation of Amyloid Deposition - Laura Atzori; Caterina Ferreli; Caterina Matucci-Cerinic; Luca Pilloni; Franco Rongioletti (MDPI AG, 2021)
Primary localized cutaneous nodular amyloidosis (PLCNA) is a rare condition due to the plasma cell proliferation and skin deposition of immunoglobulin light chains, without systemic amyloidosis or hematological dyscrasias. The association with autoimmune connective tissue diseases has been reported, especially with Sjogren's syndrome, and in a few cases with systemic sclerosis. Herein, we describe three cases of PLCNA occurring in women with a diagnosis of limited cutaneous systemic sclerosis and review the literature on the topic to highlight a stereotypical presentation. Moreover, we support the usefulness of dermoscopy, characterized by a yellow-orange waxy pattern surrounded by telangiectasias, for a rapid and non-invasive diagnostic assessment. Thus, when asymptomatic nodules occur on lower limbs of women affected with limited systemic sclerosis, and dermoscopy identifies yellow-orange blotches, a diagnosis of PLCNA can be considered and further confirmed by histopathology. Monitoring for systemic amyloidosis development is advisable, although the risk of progression is considered very low.